A critical review of knowledge sharing in various industries and organizations - Muhammad Ashraf, Fauzi; Norazha, Paiman (IJSTR, 2019)
Knowledge sharing has become the leading factor for a success in an organization . The ability to acquire and disseminate valuable knowledge for competing in the challenging market has raised the awareness to focus on the sharing of knowledge among employees. The nature of knowledge whether explicit or tacit has paved the way for a new dimension of method of sharing in many industries. The ability of an organization to retain and acquire new knowledge enables it to outperform and compare to others and determine its sustainability. Tacit knowledge, being the hardest to retain, requires a different way of disseminating knowledge and method of sharing within different contexts of organization . This disquisition provides an in depth review on how tacit knowledge is retained and controlled in different contexts of industries, focusing on the organization all, group and individual levels. Several implications are obtained from this review, as such to promote the integration of organization all success and capability of organization in coping with the current technological advancement.